Pendekatan Tasawuf dalam Pendidikan Agama Islam - Dwi Putra Purnama Maulana; Dwi Noviani (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
Islamic religious teachings with the principles of Sufism or Islamic mysticism. This approach aims to deepen students' understanding of Islamic teachings through spiritual experiences and self-introspection. In this article, the author explores the main aspects of the Sufism approach, including the concepts of tazkiyat al-nafs (cleansing the soul), muhasabah (self-introspection), and tawakkul (complete trust in Allah). The author also discusses how the application of the Sufism approach can increase students' empowerment in facing moral and social challenges, as well as help them to develop leadership based on Islamic values. In the context of Islamic religious education, the Sufism approach provides a solid foundation for creating a deep and meaningful learning environment, which not only helps students understand religious texts, but also guides them towards spiritual growth and wisdom in everyday life. This research uses qualitative literature study methods. This article concludes that the application of the Sufism approach in various Islamic educational institutions has shown a positive impact on student character formation and academic development. Thus, the Sufism approach in Islamic Religious Education is considered an effective and holistic solution to improve the quality of Islamic religious education and form a young generation with noble and responsible morals.